A botânica no ensino fundamental: o que esperar a partir da BNCC? - Medeiros, Magna Misleiza Rodrigues (2024)
The process of teaching biological content is permeated by challenges, as this area is full of abstraction and scientific terms far from the student's reality. Among the contents that address such issues, botany stands out, supporting the creation of the term botanical blindness. Using this problem, we realized the need to reflect on the aspects that govern the curriculum issues on the subject, carrying out an analysis in the Common National Curriculum Base, investigating what the document proposes about the teaching of botany for Elementary School II and what are the possible consequences. From the content analysis, it was possible to see that botany contents are, within the base, included within the same teaching unit in all years of teaching. It was also possible to notice a decrease in content, which was compacted into: cell biology, ecology, environmental impacts and reproduction. Based on this, it is concluded that the BNCC presents reduced plant content, being, in most cases, contextualized with animals. It was also noticeable the absence of content that serves as support for the study of areas that go beyond biology, which opens up possibilities for other studies that investigate botany within the new curricular configuration.